Features of the upgraded magnetic diagnostics application in the U-2M torsatron - Pashnev, V.K.; Petrushenya, A.A.; Sorokovoy, E.L.; Ozherel’ev, F.I. (Вопросы атомной науки и техники, 2019)
Modernized magnetic sensor systems have been developed and tested to carry out the magnetic measurements on the U-2M torsatron. The effect of the metallic environment, high-frequency noise and the instability of the external magnetic field in the U-2M torsatron on the readings of magnetic sensors recorded during plasma experiments were studied. Для магнітних вимірів на установці торсатрон Ураган У-2М розроблені модернізовані системи магнітних датчиків і реєструючого устаткування. Вивчено впливи металевого оточення, радіочастотних перешкод і нестабільності зовнішнього магнітного поля в торсатроні Ураган У-2М на показання магнітних датчиків під час плазмових експериментів. Для магнитных измерений на установке торсатрон Ураган У-2М разработаны модернизированные системы магнитных датчиков и регистрирующей аппаратуры. Изучены влияния металлического окружения, радиочастотных помех и нестабильности внешнего магнитного поля в торсатроне Ураган У-2М на показания магнитных датчиков во время плазменных экспериментов.